Impacts of Formative Assessment on EFL Students’ Academic Performance at Kandahar University - Sahibzada, Javed; Himat, Abdul Nafi (American International Journal of Social Science Research, 2019)
This study investigated the implementation of formative assessment and its impacts on EFL students’ academic performance at Kandahar University. The study is descriptive in nature; quantitative questionnaire was used to collect data from one hundred and fifty EFL students at all four levels selected through random sampling method. The collected data was analyzed by using IBM 24 version of SPSS and results are reported in tables by showing means, standard deviation, percentage and frequency. The major findings revealed that teachers are using formative assessment as part of their plan, allocating time for peer feedback, methods and tools of assessment teachers are using are group work, assignment, homework, presentation, project work which had positive impacts on students’ academic performance and improved final exam grades. Study also disclosed that teachers are valuing more summative assessment than formative, some important methods of assessment are ignored by teachers aversively affected their lower performance.